Perbedaan Efektivitas Terapi Audiovisual Dan Coolpack Terhadap Tingkat Nyeri Pada Prosedur Pengambilan Darah Anak Usia Pra Sekolah - Ariesta Danianti; Sri Hartini Mardi Asih; Ratnasari Ratnasari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Pain is an unpleasant sensory-nervous response experience associated with tissue damage. Pain in children during invasive procedures that are not handled properly can make them uncooperative and refuse action, which can hinder the treatment process. Long-term effects that can arise if a child's pain is not reduced or treated are the psychological and physical stress suffered by the child, such as insomnia, depression, changes in appetite, and fatigue. Efforts to overcome pain during blood sampling procedures include audiovisual therapy and cool packs. This study aims to analyze the differences in the effectiveness of audiovisual therapy and cool packs on pain levels during blood sampling procedures in preschool children. This research is quantitative with a quasi-experimental two-group posttest design. The number of samples in this study was 44 respondents, who were divided into two groups using the consecutive sampling technique. Based on the Mann- Whitney test, the results showed that there were differences in the effectiveness of audiovisual therapy and cool packs on pain levels in blood sampling procedures for preschool children, with a p-value of 0.000 (<0.05). Audiovisual therapy and cool packs can be used as nursing actions to reduce pain during blood sampling procedures in preschool children.